Toxicity of Standardized Ethanolic Extracts from Duchesnea indica (Jacks.) Focke Plants Using the BSLT Method - Waris, Risda; Handayani, Selpida; Wisdawati; Hossani, Rahni (Window of Health : Jurnal Kesehatan, 2024)
Duchesnea indica (jacks. ) focke., known as a medical plant that is used as raw ingredients for traditional medicines and herbs to increase the immune system because plants have the properties to cure and prevent various diseases. The objective of this study is to examine the quality of the duchesnea indica leaves extract by standardization method of specific and non specific parameters as well as the toxicity assay using using the Brine Shrimp Letality Test (BSLT). The results of specific parameter research include the identity of extracting duchesnea indica, Organoptic tests form extract samples that are used to extract thick, It's brown, Typical smell, astringent taste. The content of water soluble compounds is 18.67%, the content of ethanol soluble compounds is 0.03%, based in phytochemical screening test, the duchesnea indica leaves extract contain phenolic, flavonoid, tannin, Saponin and terpenoid. Non-specific parameters carried out include loss on drying of grounded Duchesne indica leaves at 0.029%, loss on drying of DuchesneA indica leaves extract at 0.026%, specific gravity determination at 0.83%, extract water content determination of 2.15%, total ash content is 3.70%, non-soluble acid of ash content is 1.32%. Thus, from these results, we can conclude that Duchesne indica leaf extract meets quality standards for extracting raw materials that can be used for traditional medicine. Research results: The standardized ethanol extract of duchesnea indica leaves is toxic to Artemia salina leach larvae.